1997
DOI: 10.1103/physrevb.55.12566
|View full text |Cite
|
Sign up to set email alerts
|

Electronic energy spectra in antiferromagnetic media with broken reciprocity

Abstract: Electronic energy spectra ͑q͒ of antiferromagnetically ordered media may display nonreciprocity; that is, the energies corresponding to Bloch states with wave numbers q and Ϫq may be different. In this paper a simple Kronig-Penney model, which includes a staggered microscopic magnetic and electric fields of the proper symmetry, is employed to estimate the magnitude of nonreciprocity effects in systems such as antiferromagnetically ordered crystals as well as periodical layered structures. ͓S0163-1829͑97͒06318-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Magneto-optic materials have been used in the bulk optics regime as the basis for optical isolators and circulators, however these devices can not be scaled to the dimensions of compact integrated analogs of microelectronic circuits due to very weak intrinsic magneto-optic response even in the case of the most favorable MO materials. It has been postulated that in order to satisfy a sufficient condition to ensure spectral nonreciprocity ω(-k) ≠ ω(k) breaking both space-and time-reversal symmetry is required 8 . Based on this criterion which constitutes just a necessary condition for spectral asymmetry it has been shown that one can employ a proper 1D periodic arrangement of magnetic and dielectric components that give rise to strong spectral asymmetry 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Magneto-optic materials have been used in the bulk optics regime as the basis for optical isolators and circulators, however these devices can not be scaled to the dimensions of compact integrated analogs of microelectronic circuits due to very weak intrinsic magneto-optic response even in the case of the most favorable MO materials. It has been postulated that in order to satisfy a sufficient condition to ensure spectral nonreciprocity ω(-k) ≠ ω(k) breaking both space-and time-reversal symmetry is required 8 . Based on this criterion which constitutes just a necessary condition for spectral asymmetry it has been shown that one can employ a proper 1D periodic arrangement of magnetic and dielectric components that give rise to strong spectral asymmetry 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the possibility of attaining ultra-low-loss light propagation with both absorption and scattering losses suppressed may be employed in construction of the ideal optical waveguide made of low-loss hollow core for telecom applications [8]. The prediction of Haldane of Raghu [3] as well as its experimental verification by Wang et al [6] are based on a strict condition that requires breaking both spaceand time-reversal symmetry [9] in order to ensure spectral nonreciprocity ω(-k) ≠ ω(k) . To satisfy limitations on symmetry several different approaches based on proper spatial arrangement of magnetic and dielectric components with strong anisotropy have been proposed to achieve non-reciprocity in 1D MOPhCs [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of frozen modes and electromagnetic unidirectionality first emerged within the context of spectral asymmetry of nonreciprocal periodic structures [5][6][7]. In this regard it was recognized that magnetic photonic crystals satisfying certain symmetry conditions [7,8] can develop a strong spectral asymmetry ω( k) = ω(− k).…”
mentioning
confidence: 99%
“…In this regard it was recognized that magnetic photonic crystals satisfying certain symmetry conditions [7,8] can develop a strong spectral asymmetry ω( k) = ω(− k). An example case of such periodic arrangement is shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation